Immune Cells Function and Activation in Response to Carica Papaya L. Consumed by Healthy Individuals - Loh, Chiew Yee (2011)
The immune system protects the human from various disease-causing agents through a complex network of cells and biochemical products. There are several factors which can affect our immune functions negatively such as stress level, environmental pollution exposure, aging, diseases, and immune-suppressive drugs. Health supplements and conventional therapy are costly andhave shown adverse side-effects. Many seek alternative ways to enhance our immune system . Natural fruits and vegetables contain rich sources of phytochemicals and have immunomodulatory effect on our immune system. Furthermore, as whole food may have beneficial synergistic properties. Carica papaya has been shown to contain a wide variety of vitamins, flavonoids, proteins and enzymes with no side-effects upon consumption. It is also widely used in traditional medication and has anti-inflammatory effects. Therefore, C. papaya was chosen to study its effect on our immune cells function and activation. Thirteen healthy individuals were put on a controlled diet. No papaya was given in the first two days, but papaya was supplemented with each meal on the third and fourth day. On the morning of the third and fifth day, whole blood samples were taken. These samples were taken to study the activity of natural killer cell cytotoxicity, neutrophil function, cell proliferation and intracellular cytokine production using flow cytometry methods. Overall results showed that C. papaya enhanced the cytotoxicity of NK cells and increased the oxidative burst in neutrophils. In addition, CD3+ lymphocytes and CD14+ monocytes proliferation were seen to increase upon stimulation with phytohemagglutinin (PHA) and lipopolysaccharide (LPS), respectively, even though CD16+ granulocytes were observed to decrease after stimulation with phorbol 12-myristate 13-acetate (PMA). We also showed the number of CD3+ proliferation in peripheral blood mononuclear cells (PBMC) stimulated with PHA determined using the flow cytometry method significantly correlated with the rate of cell proliferation measured using the tritiated thymidine incorporation assay method, making the flow cytometry method a possible alternative to the conventional method. There was a significant increase in CD4+IL-4+ (Th2) cells (p = 0.04, n = 13) after C. papaya consumption consistent with an anti-inflammatory property. The increase of Th2 cells corresponded to a decrease in CD4+IFN-γ+ (Th1) cells (p = 0.03, n = 13). Results also showed that CD3-56+ NK cells and CD3-19+ B cells decreased after C. papaya consumption. Differences were also observed between genders but results were not significant. Thus, we observed the immunomodulatory effect of C. papaya consumption on various immune cells function and activation verifying the various beneficial effect of this fruit. These results lay a foundation for future study of the mechanism of action of fruits and vegetables on the immune system.